A revision of eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). VII. Six new species and faunistic records from Middle Asia, Himalayan Region and China - Shavrin, Alexey V. (Zootaxa, 2023)
Seven species of the genus Anthobium Leach, 1819 from the eastern Palaearctic Region are (re-) described and illustrated: Nepalese A. jaegeri Shavrin & Smetana, 2019 of the consanguineum group, A. schawalleri sp. n. (China, Gansu: Lianhuashan) of the convexior group, A. ruzickai sp. n. (China, Yunnan: Biluo Mts.) of the crassum group, and a. faillei sp. n. (Nepal, Myagdi Khola), A. luteolum sp. n. (Nepal, Kulanga Khola), A. pauxillum sp. n. (Nepal, Solukhundu) and A. wittmeri sp. n. (India, Kashmir) of the fusculum group. Distributional maps for all (re-) described species are provided. Key to species of the Fusculum group is modified. Faunistic records of eleven species of the atrocephalum, fusculum, gracilipalpe, nigrum and reflexum groups are provided. Anthobium nigrum (Cameron, 1924) is recorded from Nepal for the first time. A checklist of species of the eastern Palaearctic Region is provided.